Pengelolaan Program Tahfidzul Quran di Dayah Madrasah Ulumul Qur’an Pagar Air Aceh - Afra Nadila; Lailatussaadah Lailatussaadah; Muhammad Faisal (Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia., 2022)
This research is motivated by the importance of tahfidz program management activities at Dayah MUQ Pagar Air as the integrity of the oldest tahfidz institution in Aceh, in order to survive the many applications of tahfidz programs that have sprung up in educational institutions, especially in Aceh. The purpose of this study is to describe the management of the tahfidz program. The method used is descriptive qualitative with data collection techniques using observation, interviews and documentation. The subjects in this study were Dayah Leaders, Head of Tahsin and Tahfidz Divisions, Ustadz/Ustadzah, and Santri. Data analysis starts from data collection, data reduction, presentation and drawing conclusions. The results of the study: The management of the tahfidz program includes (1) planning activities by analyzing program needs, setting goals, being in charge, costs, time and place. (2) Implementation is carried out by dividing intensive and regular classes. (3) Supervision by musyrif/ah by supervising program activities. (4) Evaluation is carried out through the development of the number of students' memorization and the quantity of tahfidz teachers. The application of the management function to the management of the tahfidz program if carried out properly, the success of achieving the number of hafidz-hafidzah 30 juz increases every year.